On the interpolation of periodic meromorphic functions - Tėvelis, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Tевялис. Об интерполировании мероморфных периодических функций V. Tėvelis. Apie periodinių meromorfinių funkcijų interpoliavimą